Crude Anthrax Protective Antigen Enhances Immunity For Salmonella Typhimurium in Mice - Lafta, Inam J.; Al abbody, Huda H. (Journal of the Faculty of Medicine Baghdad, 2017)
Background:Non-host-adapted Salmonella serovar Typhimurium is a facultative intracellular bacterium, which invades and multiplies within mononuclear phagocytes in liver, spleen, lymph nodes and Peyer’s plaques. Salmonella infection is a crucial medical and veterinary problem globally. S. Typhimurium causes various clinical symptoms, from asymptomatic infection to typhoid-like syndromes in infants or highly susceptible animals, for instance mice.Objective: The present study was carried out to investigate the efficacy of anthrax protective antigen (PA)as a potent adjuvant mixed with killed Salmonella Typhimurium (S.T.) to enhance the immunization capacity of the last.Materials and Methods: Two groups of mice were immunized with either the mixture of S.T. and PA or S.T. alone, in addition to a control group immunized with phosphate buffered saline. Skin test and ELISA test were performed to evaluate cell-mediated and humoral immunity, respectively.Results: The mixture group showed the best results in cell-mediated immunity.Furthermore, ELISA reading 14 days from booster dose was higher in the mixture group than S.T. alone. The mixture revealed high Ab titres compared to control or S.T. cohort 53 days from the beginning of immunization.These results were verified by histopathological examination.Conclusions: Our findings suggest anthrax PA as a suitable and robust adjuvant for inactivated Salmonella Typhimurium vaccine in mice.